Students' Difficulties in Learning English Phonology among Fourth Semester Students of the English Education Department - Yani Lubis; Karunia Amanda Z; Shinta Nurfidha (CV. KAMPUS AKADEMIK PUBLISING, 2026)
English phonology is an important subject in the English Education Department because it helps students understand the sound system of the English language. Through the study of phonology, students learn about speech sounds, phonetic symbols, stress, and intonation. However, many students still encounter difficulties in learning English phonology due to the complexity of its concepts and the differences between English and their first language. This study aims to identify the difficulties experienced by fourth-semester students of the English Education Department in learning English phonology and to explore the factors that contribute to those difficulties. This study employs a descriptive qualitative approach. The participants are fourth-semester students of the English Education Department who have taken phonology-related courses. Data are collected through questionnaires and interviews to obtain information about students' learning experiences. The findings are expected to show that students face difficulties in understanding phonetic transcription, distinguishing English speech sounds, applying stress and intonation patterns, and pronouncing unfamiliar sounds. In addition, factors such as limited practice, lack of confidence, and first-language influence may contribute to these difficulties. The results of this study are expected to provide useful information for lecturers and students in improving the teaching and learning process of English phonology.